A comparative study of simple and choice reaction time in Parkinson's, Huntington's and cerebellar disease. Issue 11 (November 1993) - Jahanshahi, M; Brown, R G; Marsden, C D
Abstract : The aim of the study was to compare the quantitative and qualitative similarities and differences in the performance of patients with Parkinson's disease, Huntington's disease and cerebellar disease on a number of reaction time tasks. Simple reaction time (SRT), uncued and fully cued four choice (CRT) tasks were performed by eight patients with Parkinson's disease after withdrawal of dopaminergic medication for an average of 14.4 hours; by seven non-demented patients with Huntington's disease and by eight patients with cerebellar disease. An S1 (warning signal/precue)-S2 (imperative stimulus) paradigm was used in all tasks, with the S1-S2 interval randomly varying between 0, 200, 800, 1600 and 3200 ms across trials. The patients with Huntington's disease had a significantly longer SRT than those with Parkinson's disease. None of the other group differences in uncued and unwarned SRT and CRT was significant. For the patients with Parkinson's disease and those with cerebellar disease, unwarned SRT was faster than uncued and unwarned CRT. For the patients with Huntington's disease, this CRT/SRT difference was not significant. A warning signal before the imperative stimulus resulted in a reduction of reaction time in all three groups. Advance information provided by S1 about the response that would be required by S2 was used by patients in all three groups, evident from reaction times in the fully cued CRT task being faster than those in the uncued CRT condition. Patients with cerebellar disease had slower movement times in the SRT and CRT conditions compared with the patients with Parkinson's disease and Huntington's disease, whose times did not differ. In one SRT condition, when the absence of a warning signal was predictable, patients with cerebellar disease, and to a lesser extent those with Huntington's disease, were able to maintain a general motor readiness before the imperative stimulus. This was not the case for the patients with Parkinson's disease who seemed more dependent on the presence of a warning signal to reduce their reaction time. With a few exceptions, the pattern of results of the three groups were qualitatively similar. It may be concluded that similar reaction time deficits are found in Parkinson's disease, in patients with other disorders of the basal ganglia (Huntington's disease), as well as those with a disease sparing the basal ganglia (cerebellar disease). The non-specific slowness observed at the behavioural level may, however, have diverse central mechanisms.